Uma colecção de escultura italiana, da segunda metade do século XIX, no Museu do Palácio Nacional da Ajuda - Gaspar, Ana Paula (2019)
ABSTRACT: The nineteenth century was a century of resurgence of a classical art with Greek and Roman origins. The fact that an area such as archeology has begun the excavaons of the ancient city of Pompeii in Italy reveals a set of works of art and ways of life from a period prior to the Jewish and Catholic period of a Europe of the Century XIX. Several quesons arise at the level of neoclassical thought of this period. Thus, we see the emergence of works of art inspired by classical themes of Greek mythology and whose representaons of this period include myths such as Leda, the Muse Inspiring, the Musidora, the myth of Andromeda, among others. In this context we developed an invesgaon and found 17 sculptural pieces of Italian origin that arrived in Lisbon by boat from various Italian arsts of this period. These pieces originated mainly from the order of the queen of Portugal D. Maria Pia de Sabóia, daughter of King Vitor Emanuel II of Italy, during the second half of the nineteenth century. Taking into account the process of ordering, moving, traveling and used material, the marble of Carraca, as well as the themes represented, it was possible to develop a research process of this museological nucleus and to present ways of life of these artists, inspirations, techniques and ways of carving during this historical period, as well as payment procedures and also the costs of the works acquired by the Portuguese crown during the second half of the nineteenth century. This collection is currently at the Museum of Ajuda National Palace and was the subject of an investigation and systematization of its artistic and historical importance in Portugal.